2021
DOI: 10.7759/cureus.13634
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Preterm Birth Rate During COVID-19 Lockdown in a Tertiary Care Hospital, Riyadh

Abstract: Background On March 3, 2020, the first case of coronavirus disease (COVID-19) was reported by the Ministry of Health, Kingdom of Saudi Arabia. Within days, the government confirmed more cases and adopted lockdown measures with travel restrictions from March to June 2020. A distinctive coronavirus was isolated from 190,823 patients by June 30. The pandemic resulted in a significant risk to public health. The study aimed to evaluate the impact of COVID-19 lockdown on the rate of premature births. Method In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Of 11 875 records in the initial search, 53 articles were eligible for inclusion, of which 52 were used in the quantitative synthesis 2,7–10,18–66 (Figure 1). Forty full‐text reports were excluded: reasons for the exclusions are provided in Appendix S2.…”
Section: Resultsmentioning
confidence: 99%
“…Of 11 875 records in the initial search, 53 articles were eligible for inclusion, of which 52 were used in the quantitative synthesis 2,7–10,18–66 (Figure 1). Forty full‐text reports were excluded: reasons for the exclusions are provided in Appendix S2.…”
Section: Resultsmentioning
confidence: 99%
“…Of 9953 records in the initial search, 45 articles were eligible for inclusion, of which 44 were used in the quantitative synthesis 2 , 6 , 7 , 8 , 9 , 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 (Figure 1 ). Twenty‐six full‐text reports were excluded: reasons for the exclusions are provided in Appendix S2 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the devastating morbidity and mortality arising directly from COVID-19, 29,30,[34][35][36] there have been indirect negative effects on various health outcomes. 20,21,26,28 In the case of asthma, however, COVID-19erelated public health measures during the initial months of the pandemic reduced disease burden. [23][24][25]27,37,38 As a continuation of our previous initial observations, 23 the in-depth analyses of the effects of COVID-19erelated public health measures on asthma activity over a longer period of time provide a unique opportunity to study the environmental triggers of asthma exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The institution and modulation of COVID-19erelated public health measures offer a unique opportunity to study their effects on health outcomes beyond those directly infected, including asthma. 20,21 Asthma symptoms and exacerbations decreased during the early stages of the COVID-19 pandemic, [22][23][24][25] along with factors that impact asthma, such as respiratory viral infections. 23,[26][27][28][29] In a previous publication, we found that during the first 2 months following public health interventions in Philadelphia, in-person asthma visits and steroid prescriptions decreased by more than 80%, with a concomitant decrease in rhinovirus infections and no change in air pollution compared with historical data for the years 2015-2019.…”
Section: Introductionmentioning
confidence: 99%